2019
DOI: 10.1111/cas.14135
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated fibroblast‐derived interleukin‐1β activates protumor C‐C motif chemokine ligand 22 signaling in head and neck cancer

Abstract: Oral cancer, a subtype of head and neck cancer, is characterized by increased infiltrating regulatory T cells (Treg); however, the pathological significance of the increase in Tregs in disease prognosis and progression and their underlying mechanism remain unestablished. C‐C motif chemokine ligand 22 (CCL22) has been implicated in the recruitment of Tregs. We used RT‐qPCR to determine CCL22 mRNA expression in clinical specimens and cultured cells. Loss‐of‐function and gain‐of‐function studies were carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Previous studies reported that CCL22 could recruit FOXP3 (+) regulatory T-cells. Increased CCL22 mRNA levels are correlated with increased FoxP3 mRNA levels in oral cancer specimens [43]. In a B16F10 melanoma model, imiquimod (IQM) has been shown to reduce T-regs at the tumor site by the downregulation of CCL22 production [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that CCL22 could recruit FOXP3 (+) regulatory T-cells. Increased CCL22 mRNA levels are correlated with increased FoxP3 mRNA levels in oral cancer specimens [43]. In a B16F10 melanoma model, imiquimod (IQM) has been shown to reduce T-regs at the tumor site by the downregulation of CCL22 production [44].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the source of CCL22. For instance, Huang et al proved that CCL22 was overexpressed in head and neck cancer cells [43]. CCL22 was found in macrophages of tongue squamous cell carcinoma [46].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IL-1β plays an important role in tumor microenvironment. IL-1β can increase the proliferation of dysplasia oral cells, stimulate oncogenic cytokines, and promote aggressiveness of OSCC [39,57]. Similar to the abovementioned genes, MMP2 was found to be overexpressed in HNSCC.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, the four overlapping target genes of miR-7977 (CCL22, STK4, HSPA1B, and ACTR2) in all three databases were reported to have a key role in cancer formation and metastasis. Studies have shown that these genes are involved in the growth, invasion, and metastasis of a variety of tumors, and that they play a key role in tumorrelated molecular mechanisms (30)(31)(32)(33). Furthermore, abnormal signaling pathways also play crucial roles in the development of cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%